SHOX2 promotes prostate cancer proliferation and metastasis through disruption of the Hippo-YAP pathway - Wenjie Yang; Hualin Chen; Lin Ma; Jie Dong; Mengchao Wei; Xiaoqiang Xue; Yingjie Li; Zhaoheng Jin; Weifeng Xu; Zhigang Ji (iScience, 2023)
Summary: The transcription factor SHOX2 gene is critical in regulating gene expression and the development of tumors, but its biological role in prostate cancer (PCa) remains unclear. In this study, we found that SHOX2 expression was significantly raised in PCa tissues and was associated with clinicopathological features as well as disease-free survival (DFS) of PCa patients. Phenotypic tests showed that the absence of SHOX2 inhibited PCa growth and invasion, while SHOX2 overexpression promoted these effects. Mechanistically, SHOX2 was found to activate the transcription of nephronophthisis type 4 (NPHP4), a gene located downstream of SHOX2. Further analysis revealed that SHOX2 could potentially interfere with the Hippo-YAP signaling pathway through NPHP4 activation, facilitating the oncogenic behavior of PCa cells. These findings highlight SHOX2 as an oncogene in PCa and provide a basis for developing potential therapeutic approaches against this disease.